2018
DOI: 10.1080/14763141.2018.1433872
|View full text |Cite
|
Sign up to set email alerts
|

The load-velocity profile differs more between men and women than between individuals with different strength levels

Abstract: This study aimed to determine the suitability of the load-velocity relationship to prescribe the relative load (%1RM) in women, as well as to compare the load-velocity profile between sexes and participants with different strength levels. The load-velocity relationship of 14 men (1RM: 1.17 ± 0.19) and 14 women (1RM: 0.66 ± 0.13) were evaluated in the bench press exercise. The main findings revealed that: (I) the load-velocity relationship was always strong and linear (R range: 0.987-0.993), (II) a steeper load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
72
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(95 citation statements)
references
References 26 publications
17
72
1
5
Order By: Relevance
“…Although lower body muscular strength was not measured in the current study, maximal strength has been shown to be a limiting factor in jumping ability and other lower body measure of explosive strength (Andersen & Aagaard, 2006;Suchomel et al, 2018). Previous research has demonstrated that males possess greater maximal strength and ability to produce greater velocities at the same percentage of one repetition maximum than their female counterparts (Sole et al, 2018;Torrejon et al, 2019). When comparing the force-time curves in the countermovement jump between sexes, previous research has reported that the male and female differences in countermovement jump height were attributed to force characteristics and not temporal characteristics of the force-time curve (Beckham et al, 2019;Sole et al, 2018).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Although lower body muscular strength was not measured in the current study, maximal strength has been shown to be a limiting factor in jumping ability and other lower body measure of explosive strength (Andersen & Aagaard, 2006;Suchomel et al, 2018). Previous research has demonstrated that males possess greater maximal strength and ability to produce greater velocities at the same percentage of one repetition maximum than their female counterparts (Sole et al, 2018;Torrejon et al, 2019). When comparing the force-time curves in the countermovement jump between sexes, previous research has reported that the male and female differences in countermovement jump height were attributed to force characteristics and not temporal characteristics of the force-time curve (Beckham et al, 2019;Sole et al, 2018).…”
Section: Discussionmentioning
confidence: 71%
“…This is a concern as previous research has established differences in force and power capabilities between males and females in other athletic activities (McMahon, Rej & Comfort, 2017;Rice et al, 2017). For example, a number of studies has observed that males are able to produce higher velocities at the same percent of one repetition maximum and have a greater rate of force development and countermovement jump height than females (Laffaye, Wagner & Tombleson, 2014;McMahon, Rej & Comfort, 2017;Rice et al, 2017;Torrejon et al, 2019). Rice et al (2017) concluded that this greater jump height observed in males compared to females can be attributed to larger concentric impulse and thus greater velocity throughout most of the concentric phase at take-off in the countermovement jump.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst several VBT approaches exist, recent research has encouraged the use of individualised load-velocity relationships. [12][13][14] This method involves obtaining concentric velocity data across the loading spectrum and establishing velocity thresholds at each relative load, which are then used to modify subsequent training load. Dorrell et al 15 recently reported that six weeks of prescribing training load based on generalised velocity zones led to greater improvements in countermovement jump (CMJ) height than PBT in 16 recreationally-trained men.…”
Section: Introductionmentioning
confidence: 99%
“…In the bench press throw, women achieve peak power output at 30-50%, whereas men at 30% (Thomas et al, 2007). Moreover, another study indicated that men achieved higher mean velocity for light loads, whereas women reported higher mean velocity for heavy loads during the BP on a Smith machine (Torrejón et al, 2018). These data suggest that various training strategies should be used in training for men and women to develop power output.…”
Section: Discussionmentioning
confidence: 95%